Experimental Investigation on the Water Yield from Snow by Means of Radioactive Cobalt - Kuzmin,P. P. (1965)
The article has reviewed data from the first experiment for study of water loss from the snow in an undisrupted snow cover by the use of radioactive cobalt. The objective was to determine the possibility of using the gamma method for this purpose. The article also gives an evaluation of the effectiveness of other methods for experimental determination of the water loss by the water balance method, heat balance of the snow cover method, runoff (impermeable) areas, P. A. Uryvayev apparatus and the Central Institute of Forecasts movable 'platform'. (Author) Trans. of Gosudarstvennyi Gidrologicheskii Institut. Trudy (USSR) n65 p30-49 1958.